Blood rush : the dark history of a vital fluid - Verplaetse, Jan (Reaktion Books, 2020)
As a young man Jan Verplaetse saw a hare suspended from a meat hook, skinned and gutted. What struck him so forcefully at the time was not the animal but the blood gently dripping from its mouth. His reaction prompted the start of a quest he undertakes in this book - to investigate our fascination with blood, the most vital of fluids. Blood Rush shows how, throughout history, blood has had the capacity to intoxicate us. In his deeply researched and provocative narrative, Verplaetse moves from antiquity to the present, from magic to experimental psychology, from philosophy to religion and scientific discoveries, to demonstrate why blood both repels and attracts us.